Peran Problem-Focused Coping dan Family Protective Factors dalam Membangun Resiliensi Orangtua Anak Berkebutuhan Khusus - Agustina, Menik Tetha; Trisnadewi, Benedicta Audrey Putri; Kumalasari, Ervina (Jurnal Psikologi Integratif, 2025)
Parents of children with special needs face ongoing challenges, including high caregiving demands, prolonged stress, and the need to adjust parenting expectations. This study examines the role of problem-focused coping and family protective factors in predicting parental resilience. Participants were 83 parents of children with physical or psychological developmental disorders receiving services at YPAC Semarang, selected through purposive sampling. Data were collected using the Inventory of Family Protective Factors (IFPP), Brief-Coping Orientation to Problems Experienced Inventory (Brief-COPE), and the Connor-Davidson Resilience Scale (CD-RISC). Pearson correlation analysis showed that problem-focused coping and family protective factors were positively associated with resilience (r = .317 and r = .153). Multiple regression analysis indicated that both variables significantly predicted parental resilience simultaneously (R = .371, p < .01), contributing 13.8% of the variance (R² = .138). The findings suggest that parental resilience is a multidimensional construct influenced by coping strategies, family strengths, and other psychological and contextual factors. Strengthening problem-focused coping and enhancing family protective factors may therefore support resilience development among parents of children with special needs.   Orang tua anak berkebutuhan khusus menghadapi tuntutan pengasuhan yang tinggi, stres berkepanjangan, serta penyesuaian strategi pengasuhan. Penelitian ini bertujuan menganalisis peran koping berfokus masalah dan faktor perlindungan keluarga terhadap resiliensi orangtua. Subjek penelitian berjumlah 83 orang tua anak dengan gangguan perkembangan fisik atau psikologis di YPAC Semarang yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan IFPP, Brief-COPE, dan CD-RISC. Hasil analisis korelasi menunjukkan hubungan positif antara koping berfokus masalah dan faktor perlindungan keluarga dengan resiliensi (r = .317; r = .153). Analisis regresi berganda menunjukkan kedua variabel secara simultan memprediksi resiliensi secara signifikan (R = .371; p < 0,01) dengan kontribusi sebesar 13,8% (R² = .138). Hasil penelitian menegaskan bahwa resiliensi orangtua merupakan konstruk multidimensional yang dipengaruhi oleh strategi koping, kekuatan keluarga, dan faktor psikososial lainnya. Oleh karena itu, penguatan koping adaptif dan faktor perlindungan keluarga penting dalam meningkatkan resiliensi orangtua anak berkebutuhan khusus.